A new species, and a new distribution record for the genus Sympleurotis Bates, 1881 (Coleoptera, Cerambycidae, Lamiinae) from Mexico - Noguera, Felipe A.; Gutiérrez, Nayeli; Monné, Miguel A. (Zootaxa, 2018)
A new species of the genus Sympleurotis Bates from Jalisco, Mexico is described and illustrated. Details of a new state record of Sympleurotis rudis Bates, 1881 from Chiapas, Mexico is also included.